2012
DOI: 10.1159/000341993
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use and Hazardous Drinking among Medical Specialists

Abstract: Background: Alcohol use among medical specialists remains a delicate topic. However, the number of prevalence studies remains very limited in Western European countries. Aims: To explore alcohol use and hazardous drinking among male and female medical specialists. Methods: All medical specialists in Belgium – a typical Western European country regarding alcohol use – were invited to participate. Alcohol use and abuse were measured using the Alcohol Use Disorder Identification Test (AUDIT) and the CAGE screen (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 32 publications
6
30
1
Order By: Relevance
“…[ 34 35 ] In this study, none of the females used alcohol hazardously; nevertheless, there was no significant relationship between hazardous alcohol use and gender. Similarly, other studies have reported a lower rate of hazardous/harmful drinking among female doctors[ 12 28 29 ] and other population. [ 30 ] The lower number of females with alcohol use and the absence of female gender reported with hazardous alcohol use in this study may have been influenced by culture and religion.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…[ 34 35 ] In this study, none of the females used alcohol hazardously; nevertheless, there was no significant relationship between hazardous alcohol use and gender. Similarly, other studies have reported a lower rate of hazardous/harmful drinking among female doctors[ 12 28 29 ] and other population. [ 30 ] The lower number of females with alcohol use and the absence of female gender reported with hazardous alcohol use in this study may have been influenced by culture and religion.…”
Section: Discussionsupporting
confidence: 55%
“…However, this is rather at variance with most findings in most Western countries. [ 3 6 26 27 28 ] For example, in a study by Rosta in Germany,[ 26 ] majority were moderate drinkers, only 9.5% were abstainers and with about 20% being hazardous drinkers similar to 18.5% reported by Joos et al [ 29 ] in Belgium. Nonetheless, the proportion of doctors who were risky drinkers is lower compared with what obtained in the general population and patient population in Nigeria.…”
Section: Discussionmentioning
confidence: 94%
“…14 A Belgian survey of 1500 medical specialists of all kinds, 29 based on the research model, showed comparable results with respect to smoking prevalence (8%) and drinking habits (95%). Specialists were more likely to drink alcohol on a daily basis compared with GPs (20% versus 14%) and used anxiolytics more often (9% versus 5%).…”
Section: Comparison With Existing Literaturementioning
confidence: 97%
“…It is medical workers -doctors in particular -who play the key role in popularizing knowledge on healthy lifestyle in our society. But in spite of that behavioral risk factors are widely spread among practical healthcare workers [1,2,3,10,11,12,13].…”
Section: ____________________________________________________________mentioning
confidence: 99%